2013
DOI: 10.1002/htj.21073
|View full text |Cite
|
Sign up to set email alerts
|

MHD Flow and Heat Transfer of a Dusty Fluid Over a Stretching Hollow Cylinder with a Convective Boundary Condition

Abstract: In this study, we deal with the problem of a steady two‐dimensional magnetohydrodynamic (MHD) flow of a dusty fluid over a stretching hollow cylinder. Unlike the commonly employed thermal conditions of constant temperature or constant heat flux, the present study uses a convective heating boundary condition. The multi‐step differential transform method (multi‐step DTM), one of the most effective methods, is employed to find an approximate solution of the system of highly nonlinear differential equations govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Sivaraj and Kumar [69] studied time‐dependent viscoelastic fluid conveying dust in a closed irregular channel when mass diffusion is not a constant property and observed that unsteadiness, chemical reaction, and Biot number due to convectively heated surface strongly influence the dynamics of the dusty fluid. Rasekh et al [61] studied the dynamics of dusty fluid subject to a significant magnetic field strength over a cylinder due to stretching and convectively heated walls. Ramesh and Gireesha [59] examined the increasing thermal radiation effect on the dynamics of a dusty fluid due to stretching and it was pointed out that thermal boundary layer thickness is a decreasing property of Prandtl number while dust's temperature is a decreasing property of fluid particles interaction.…”
Section: Background Informationmentioning
confidence: 99%
“…Sivaraj and Kumar [69] studied time‐dependent viscoelastic fluid conveying dust in a closed irregular channel when mass diffusion is not a constant property and observed that unsteadiness, chemical reaction, and Biot number due to convectively heated surface strongly influence the dynamics of the dusty fluid. Rasekh et al [61] studied the dynamics of dusty fluid subject to a significant magnetic field strength over a cylinder due to stretching and convectively heated walls. Ramesh and Gireesha [59] examined the increasing thermal radiation effect on the dynamics of a dusty fluid due to stretching and it was pointed out that thermal boundary layer thickness is a decreasing property of Prandtl number while dust's temperature is a decreasing property of fluid particles interaction.…”
Section: Background Informationmentioning
confidence: 99%
“…The size and shape of the dust particles is uniform and spherical. With all these assumption the governing equations are ( [14], [43]):…”
Section: Introductionmentioning
confidence: 99%
“…In the expression (6) ‫ݍ‬ is denoted by Rosseland approximation [43]: Dimensionless variables are defined as [5]:…”
Section: Introductionmentioning
confidence: 99%